Integrated Approach to Modeling IC Competence in Students - A. Belevitin, V.; A. Bogatenkov, S.; V. Rudnev, V.; L. Khasanova, M.; I.Tyunin, A. (International Journal of Engineering and Technology, 2018)
A strong correlation of the problem of guaranteed information security provision with the human factor and the escalation of threats to information security for professional activity in information society prove the importance of the relevant proper training of highly qualified personnel.The theoretical justification of the integrated approach to modeling studentsâ€™ information and communication competence (IC competence), including new structure and content of students' preparation under integration of the classical system and e-learning with the development of adequate forms and methods of teaching, promotes the high level of professional competence.The scope of research is represented by the principles of computational modeling of IC competence, formed as a result of continuous staged personnel training in "Professional Education (by Industries)" based on the Federal State Educational Standard of Russia.The research offers an integrated approach to computational modeling of studentsâ€™ IC competence based on the classification of competencies demonstrating the projection of a professional competency vector on a plane of information and communication technologies (ICT plane) acting as a model of studentsâ€™ IC competence. Here, any ray of the ICT plane may act as a model of IC competence in a certain specialization of proper training of highly qualified personnel in any industry. Such an approach to IC competence of a graduate of an educational organization is determined by respective aims and fields of professional activity corresponding to IC competencies.The methodology of content design has been developed for educational disciplines in continuous information and academic training of graduates under e-learning, as well as an algorithm based on the competence approach, making it possible to explicitly determine the generation path of IC competence of professional education organization graduates having different basic training, which eliminates the threat of insufficient or excessive content of the intended study materials.Â Â